Aerobic Exercise Attenuates Pain Sensitivity: An Event-Related Potential Study - Zheng, Kangyong; Chen, Changcheng; Yang, Suyong; Wang, Xueqiang (Frontiers in Neuroscience, 2021)
In this study, electroencephalography (EEG) was utilized to explore the neurophysiological mechanisms of aerobic exercise-induced hypoalgesia (EIH) and provide a theoretical basis for the application of aerobic exercise in pain assessment and treatment. Forty-five healthy subjects were randomly divided into moderate-intensity aerobic exercise (70% heart rate reserve (HRR)), low-intensity aerobic exercise (50% HRR), or control groups (sitting). Aerobic exercise was performed with cycling. Pressure pain threshold, heat pain threshold, event-related potential (ERP) induced by contact heat stimulus and pain scoring were measured before and after the intervention. We found that moderate-intensity aerobic exercise can increase the pressure pain threshold (rectus femoris: t = -2.71, p = 0.017; tibialis anterior muscle: t = -2.36, p = 0.033) and heat pain threshold (tibialis anterior muscle: t = -2.219, p = 0.044) of proximal intervention sites rather than distal sites, and decreased pain scorings of contact heat stimulus. After moderate-intensity aerobic exercise, alpha oscillation power reflecting the central descending inhibitory function was enhanced (t = -2.31, p < 0.05). Low-intensity aerobic exercise mainly reduced the pain unpleasantness rating (Block 1: t = 2.415, p = 0.030; Block 2: t = 3.287, p = 0.005; Block 4: t = 2.646, p = 0.019; Block 5: t = 2.567, p = 0.022). Aerobic exercise had an overall EIH effect. Its hypoalgesic effect was related to exercise intensity and affected by the site and type of pain stimulus. Moderate-intensity aerobic exercise effectively reduced the sensitivity to various painful stimuli, and low-intensity aerobic exercise selectively inhibited the negative emotional pain response. The hypoalgesic mechanism of aerobic exercise involves the enhancement of the central descending inhibitory function.